Sensitivity, specificity, and diagnostic accuracy of WHO 2013 criteria for diagnosis of gestational diabetes mellitus in low risk early pregnancies: international, prospective, multicentre cohort study - Irene Hoesli; Anne Richter; Christian S Göbl; Peter Husslein; Bettina Winzeler; Mirjam Kunze; Monya Todesco Bernasconi; Evelyn A Huhn; Thorsten Fischer; Martina Kreft; Deborah R Vogt; Eva Dölzlmüller; et al. (BMJ Medicine)
Objective To evaluate the predictability of gestational diabetes mellitus wth a 75 g oral glucose tolerance test (OGTT) in early pregnancy, based on the 2013 criteria of the World Health Organization, and to test newly proposed cut-off values.Design International, prospective, multicentre cohort study.Setting Six university or cantonal departments in Austria, Germany, and Switzerland, from 1 May 2016 to 31 January 2019.Participants Low risk cohort of 829 participants aged 18-45 years with singleton pregnancies attending first trimester screening and consenting to have an early 75 g OGTT at 12-15 weeks of gestation. Participants and healthcare providers were blinded to the results.Main outcome measures Fasting, one hour, and two hour plasma glucose concentrations after an early 75 g OGTT (12-15 weeks of gestation) and a late 75 g OGTT (24-28 weeks of gestation).Results Of 636 participants, 74 (12%) developed gestational diabetes mellitus, according to World Health Organization 2013 criteria, at 24-28 weeks of gestation. Applying WHO 2013 criteria to the early OGTT with at least one abnormal value gave a low sensitivity of 0.35 (95% confidence interval 0.24 to 0.47), high specificity of 0.96 (0.95 to 0.98), positive predictive value of 0.57 (0.41 to 0.71), negative predictive value of 0.92 (0.89 to 0.94), positive likelihood ratio of 10.46 (6.21 to 17.63), negative likelihood ratio of 0.65 (0.55 to 0.78), and diagnostic odds ratio of 15.98 (8.38 to 30.47). Lowering the postload glucose values (75 g OGTT cut-off values of 5.1, 8.9, and 7.8 mmol/L) improved the detection rate (53%, 95% confidence interval 41% to 64%) and negative predictive value (0.94, 0.91 to 0.95), but decreased the specificity (0.91, 0.88 to 0.93) and positive predictive value (0.42, 0.32 to 0.53) at a false positive rate of 9% (positive likelihood ratio 5.59, 4.0 to 7.81; negative likelihood ratio 0.64, 0.52 to 0.77; and diagnostic odds ratio 10.07, 6.26 to 18.31).Conclusions The results of this prospective low risk cohort study indicated that the 75 g OGTT as a screening tool in early pregnancy is not sensitive enough when applying WHO 2013 criteria. Postload glucose values were higher in early pregnancy complicated by diabetes in pregnancy. Lowering the postload cut-off values identified a high risk group for later development of gestational diabetes mellitus or those who might benefit from earlier treatment. Results from randomised controlled trials showing a beneficial effect of early intervention are unclear.Trial registration ClinicalTrials.gov NCT02035059.